Antigenic Determinants of Possible Vaccine Escape by Porcine Circovirus Subtype 2b Viruses - Constans, Megan (Bioinform Biol Insights, 2015)
Currently available commercial vaccines against porcine circovirus strain 2 (PCV2) solely target the PCV2a genotype. While PCV2 vaccines are highly effective in preventing clinical signs, PCV2b has dominated over the PCV2a genotype in prevalence, corresponding with the introduction of PCV2a vaccines. A recently emerged PCV2b recombinant with an additional amino acid in the capsid protein, designated the mutant PCV2b (mPCV2b), is cause for concern due to its increased virulence and rapid spread. The accumulation of recent evidence for the increased genetic diversity in PCV2 suggests that current vaccines against PCV2a may be inducing selection pressure and driving viral evolution. In this study, the hypothesis that differences in key immune epitopes between the PCV2a vaccine strains, a classical PCV2b strain called PCV2b 41513 obtained from a vaccine-failure case, and mPCV2b strains could promote vaccine escape was tested using immuno-informatic tools. In the major viral proteins, 9 of the 18 predicted swine leukocyte antigens (SLA) class-I epitopes, 8 of the 22 predicted SLA class-II epitopes, and 7 of the 25 predicted B cell epitopes varied between the vaccine and field strains. A majority of the substitutions in both the T- and B-cell epitopes were located in the capsid protein. Some B- and T-cell epitopes that were identified as immunogenic in the vaccine strain were not identified as epitopes in the field strains, indicating a subtle shift in the antigenic profile of the field strains. Several nonconserved epitopes had both predicted B- and T-cell functions. Therefore, substitutions in the dual epitopes could affect both arms of the immune response simultaneously, causing immune escape. Our findings support further rational design of PCV2 vaccines to increase the current threshold of protection.